Comparison of Lohmann White and Lohmann Brown Strains in Embryo Physiology - Tona , K.; Agbo, K.; Kamers, B.; Everaert, N.; Willemsen, H.; Decuypere, E.; Gbeassor, M. (International Journal of Poultry Science, 2010)
Chicken post-hatch performance is known to be related to embryonic developmental parameters. However, strain or genotype differences with regard to embryo physiological parameters have received little attention. A total of 1,200 hatching eggs produced by Lohmann Brown (LB) and Lohman White (LW) breeders of the same age were studied. Between 62 and 150 h of incubation, eggs Resonance Frequency (RF) was measured as indicator of early embryonic development. Also, albumen pH was measured between setting and d 8 of incubation. From d 10 to 18 of incubation, remaining albumen and embryos were weighed. During the last days of incubation, hatching occurrences were monitored after every four hours and hatched chicks were recorded. Results indicate that RF of LW eggs were lower than that of LB eggs (p